Linking Halal food certification and business performance. Issue 7 (3rd July 2017) - Ab Talib, Mohamed Syazwan; Ai Chin, Thoo; Fischer, Johan
Abstract : Purpose: The purpose of this paper is to explore the relationship between Halal food certification (HFC) and business performance. This study argues that Halal food certificate implementation positively influences business performance. Design/methodology/approach: A total of 210 Halal certified food manufacturing companies in Malaysia participated in the study. Data were gathered through a structured questionnaire and were analysed using partial least squares structural equation modelling technique. Findings: The study proved that HFC has a positive relationship with operational performance. Additionally, operational performance mediates the relationship between HFC and financial performance. Altogether, this signifies that Halal food certificate implementation positively influences business performance. Practical implications: By linking HFC and business performance, managers may be aware of the significant role of HFC in influencing operational and financial performance. It would entice more food companies to become Halal certified that opens up an opportunity to a lucrative Halal food industry. It also empirically justifies that a religion-based food certification has the ability to influence business performance, consistent with other established food standards such as ISO 22000 or HACCP. Originality/value: Although numerous studies have concentrated on well-established food certifications, the expanding Muslim population, rising demand for Halal food, and lucrative Halal food market have raised the attention on HFC research among academicians and practitioners. This research is able to highlight the importance of implementing HFC among food companies as it could potentially lead to superior business outcomes.